Influence of sex and processing methods on physicochemical and organoleptic quality of rabbit meat (2012)
The objective of this study was to determine the influence of sex and processing (Cooking) methods on pysicochemical and organoleptic properties of rabbit meat. Thirty-two matured rabbits of different breeds (16 males and 16 females) were used for this study. The rabbits were purchased from Abeokuta and transported to Olabisi Onabanjo University, Yewa Campus, Ayetoro, where this study was conducted. The rabbits were rested for 2 weeks, starved for 16 h, then slaughtered and dressed conventionally. Their carcasses were assigned randomly to four cooking treatments viz: frying, broiling, roasting and stewing. 100 g of meat samples were excised from leg cuts of rabbit carcasses from each treatment and cooked for 20 min after which physical, chemical and sensory attributes of rabbit meat were determined. Data generated were subjected to analysis of variance (ANOVA) for completely randomized design with 4x2 factorial arrangement (P = 0.05). The results showed that cooking loss, thermal shortening and shear force values were higher (P < 0.05) in fried rabbit meat, while water holding capacity and cooking yield were higher (P < 0.05) in stewed rabbit meat. Moisture and protein contents were higher (P < 0.05) in stewed rabbit meat while, they were lower (P < 0.05) in fried rabbit meat. Meat from female rabbits had higher (P < 0.05) proximate component values except nitrogen free extract values that were higher (P < 0.05) in male rabbit meat. The results revealed that colour and flavour scores were higher (P < 0.05) in fried rabbit meat, followed by boiled ones also, fried rabbit meat were accepted more than broiled, roasted and stewed ones. Also, male rabbit meat was highly relished than female rabbit meat in this study. It was suggested therefore, that frying and broiling methods be employed, also male rabbits be preferred if rabbit meat is to be processed since fried and broiled rabbit meat as well as meat from male rabbits were accepted more than these from female rabbits, in this study.